Micro irrigation based optimal crop plan for Surgi lift irrigation system - CHANDRAKAR, ANKITA; PANDEY, VINAY K.; CHAKRABORTY, PARTHO P. (Journal of Soil and Water Conservation, 2022)
Water is a critical input for success of agriculture and its ever widening technology creation. Water scarcity as a risk has always been a part of agriculture and farm business. Hence, management of available irrigation water assumes great importance in the field of agriculture. This study was undertaken in a selected area of Surgi village, Rajnandgaon to determine the optimal crop plan for increasing crop productivity and farm income. The crop water requirements to irrigate 5.196 ha area was 9596.94 m3 during the crop period. Therefore, with the available resources to attain maximum yields operation schedules are planned according to the available water. So the rest of the water which is being pumped every day can be shared by the group of farmers so that their crop yields can be improved in an area of 31.575 ha. The results indicated that water and other resources were used efficiently to get optimum pattern in the cultivation of different crops.